COVID-19 Across Africa: Epidemiologic Heterogeneity and Necessity of Contextually Relevant Transmission Models and Intervention Strategies - Twahirwa Rwema, Jean Olivier (Ann Intern Med, 2020)
This commentary discusses the COVID-19 pandemic on the African continent. The authors describe why the international community should be hesitant in developing forecasts and prevention strategies for COVID-19 in the absence of integration of African data and leadership by African institutions.